Gold price forecasting by using ARIMA / Muhammad Fuad Hamzah and Khairul Nizam Abd Halim - Hamzah, Muhammad Fuad; Abd Halim, Khairul Nizam (Faculty of Computer and Mathematical Sciences, 2022)
Gold is the most popular investment in the world because it has shown to be the most effective safe haven in a lot of countries. It is difficult to use method such as technical analysis to predict the gold value. Many prediction problems that contain a time component require time series forecasting, which is an important topic of machine learning. This is a study of gold rate that will predict the gold price by using one of the time series methods which is Autoregressive Integrated Moving Average (ARIMA). The main feature of the system is to predict the gold price and visualize the predicted value in a line chart. This will help users to know the future trend and can help them to make a decision for the right time to buy or sell the gold. The system will provide other features to help users in gold investment such as get the latest gold news, calculator of gold investment and gold branch location around Malaysia.